Evaluation of the Effect of Coriandrum sativum L. Essentisal oil on Naloxone-Induced Jumping in Morphine-Dependent Mice - Shahram Saghaei; Saeid Abbasi Maleki (Fasa University of Medical Sciences, 2017)
Background & Objective: Coriandrum sativum L (CS) has different pharmacological properties such as analgesic, anti-inflammatory, and anti-stress effects. Hence, in the present study the effects of CS essential oil on naloxone -induced jumping in morphine-dependent mice was investigated. Material & Methods: In this experimental study, 60 male albino mice were used. The animals were divided into 10 groups of 6, including carrier (10 ml/kg), clonidine (3.5 mg/kg), and different doses of CS essential oil (400, 600, and 800 mg/kg). Tolerance and dependency on morphine were induced by administration of different doses of morphine (50, 50, 75, and 50 mg/kg, respectively) in a 4-day schedule. On the last day, after administration of single dose of morphine, Naloxone (5 mg /kg) was injected and the number of jumps was recorded within 30 minutes.  Results: Results showed that all doses of CS essential oil and clonidine, compared to control group, significantly decreased the number of jumping in both tolerance and dependence stage (P<0.001).Also, only high (800mg/kg) and all doses of essential oil reduced the number of jumping during tolerance and dependence stages respectively, better than clonidine . Conclusion: Based on present study findings, it is concluded that, probably the existing linalool in CS could decrease the number of jumps from tolerance and dependence in morphine- dependent mice. Of course, further studies are required to clarify their exact mechanism of action.